Primary umbilical endometriosis: A rarity - Sumit Ranjan Pramanik; Saumen Mondal; Sayanti Paul; D Joycerani (Wolters Kluwer Medknow Publications, 2014)
Endometriosis is a functional endometrial tissue found outside the normal uterine cavity. Primary umbilical endometriosis is defined as the presence of ectopic endometrial glands and stroma within umbilicus, without prior history of pelvic endometriosis. It is a rare presentation in all cases of endometriosis, especially in Asians. Here, a case of primary umbilical endometriosis has been reported in a 33-year-old nulliparous female who presented with the history of cyclical bleeding and pain in an umbilical mass during menstrual cycle. Athough the disease is rare, umbilical endometriosis should be taken into account in differential diagnosis of umbilical disorders even in young nulliparous women with no typical symptoms of pelvic endometriosis. The disease pathogenesis, its symptoms, and treatment modality have been discussed.